2018
DOI: 10.1017/s1366728918000640
|View full text |Cite
|
Sign up to set email alerts
|

A prosodic bias, not an advantage, in bilinguals' interpretation of emotional prosody

Abstract: A bilingual advantage has been found in prosody understanding in pre-school children. To understand this advantage better, we asked 73 children (6-8 years) to identify the emotional valence of spoken words, based on either semantics or emotional prosody (which were either consistent or discrepant with each other). Bilingual experience ranged from no to equal exposure to and use of two languages. Both age and bilingual experience predicted accurate identification of prosody, particularly for trials where the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 38 publications
2
21
1
Order By: Relevance
“…Namely, Champoux-Larsson and Dylman would likely have claimed to have replicated the bilingual advantage in prosody processing in children, and we would simply have concluded that the advantage in prosody processing found in bilingual children disappears in adulthood (similarly to what other studies investigating the development of alleged bilingual advantages in other domains usually find, see for example Bialystok et al, 2012). However, because the study by Champoux-Larsson and Dylman (2019) and this study also analysed the types of mistakes that the participants make, both studies show that the reality of prosody processing, in constrained contexts, is more intricate and complex than what a bilingual advantage approach could explain on its own. Furthermore, as in Yow and Markman (2011), participants were not instructed to focus specifically on one of the two cues in Part 1 of this study.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Namely, Champoux-Larsson and Dylman would likely have claimed to have replicated the bilingual advantage in prosody processing in children, and we would simply have concluded that the advantage in prosody processing found in bilingual children disappears in adulthood (similarly to what other studies investigating the development of alleged bilingual advantages in other domains usually find, see for example Bialystok et al, 2012). However, because the study by Champoux-Larsson and Dylman (2019) and this study also analysed the types of mistakes that the participants make, both studies show that the reality of prosody processing, in constrained contexts, is more intricate and complex than what a bilingual advantage approach could explain on its own. Furthermore, as in Yow and Markman (2011), participants were not instructed to focus specifically on one of the two cues in Part 1 of this study.…”
Section: Discussionmentioning
confidence: 62%
“…Another important issue is the consequences of investigating and interpreting results in different ways to support or refute the debated bilingual advantage concept. As Champoux-Larsson and Dylman (2019) showed in their study, what was originally interpreted as a bilingual advantage in the processing of EP was driven by a bias towards prosody. In the current study, we did not find that higher bilingualism scores led to better performance on the prosody trials (i.e., we did not find a bilingual advantage), but we still replicated the PB.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Third, although there is a movement toward treating bilingualism as a continuous variable that is endorsed by many (e.g., Champoux-Larsson & Dylman, 2019;DeLuca et al, 2019;Edwards, 2012;Gullifer et al, 2018;Gullifer & Titone, 2020;Incera & McLennan, 2018;Jylkkä et al, 2017;Kaushanskaya & Prior, 2015;Luk & Bialystok, 2013;Sulpizio et al, 2020;Surrain & Luk, 2019), as Kremin and Byers-Heinlein (2020) point out, there are situations where this may not be possible or preferable (e.g., with small samples). Therefore, giving up a dichotomous classification of bilingualism altogether may not be the answer when it comes to operationalizing bilingualism (Kremin & Byers-Heinlein, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, few people are either monolingual or bilingual, but rather, most fall somewhere on a range in between the two extremes. Thus, it is increasingly argued that bilingualism should be operationalized as a continuous variable in order to better reflect its true nature and thus increase the precision and sensitivity of the operationalization (e.g., Champoux-Larsson & Dylman, 2019;DeLuca, Rothman, Bialystok, & Pliatsikas, 2019;Edwards, 2012;Gullifer et al, 2018;Gullifer & Titone, 2020;Incera & McLennan, 2018;Jylkkä et al, 2017;Kaushanskaya & Prior, 2015;Luk & Bialystok, 2013;Sulpizio, Del Maschio, Del Mauro, Fedeli, & Abutalebi, 2020;Surrain & Luk, 2019, but see Kremin & Byers-Heinlein, 2020, for a suggestion on how to use both categorical and continuous approaches simultaneously based on a factor mixture model and on a gradeof-membership model). Yet, there are no systematic investigations to determine whether this can directly affect the outcomes of studies.…”
mentioning
confidence: 99%